Emerging Regulatory Challenges on The Value and Future Of Cryptocurrency Exchange Business - Ngwakwe, Collins (Acta Universitatis Danubius. Juridica, 2023)
The objective of this paper is to appraise the regulatory challenge facing the cryptocurrency industry with attendant financial value implication following the current SEC’s legal action and to provide an insight into the future of cryptocurrencies in the face of uncertain regulatory environment. The prior work inclination is on extant regulatory information, declarations, and commentaries on the cryptocurrency industry such as the SEC, the DOJ and financial publications. The approach combines a discursive analysis of documented commentaries and brief numerical share value analysis. Findings show, among others, that regulators around the world are still coming to terms with the uniqueness and intractable characteristic of cryptocurrency asset, hence current variegated regulations, and legal recognitions. Furthermore, findings show that the recent SEC’s lawsuit against Binance and Coinbase had a significant impact on their share prices and additionally caused a negative ripple on the share price of some other cryptocurrencies. The findings have implications for cryptocurrency investors and operators for investment and strategic policy decisions in the face of uncertainty in cryptocurrency regulatory environment. It also provides a useful current case study for business schools and an agenda for further study with a larger pool of cryptocurrency companies facing regulatory threat. The paper contributes a novel weaving of financial ramifications of uncertain regulatory actions on cryptocurrency companies.